Catalytic effects of molybdate and chromate–molybdate films deposited on platinum for efficient hydrogen evolution. Issue 5 (10th March 2023) - Diaz‐Morales, Oscar; Lindberg, Aleksandra; Smulders, Vera; Anil, Athira; Simic, Nina; Wildlock, Mats; Alvarez, Germán Salazar; Mul, Guido; Mei, Bastian; Cornell, Ann
Abstract: BACKGROUND: Sodium chlorate (NaClO3 ) is extensively used in the paper industry, but its production uses strictly regulated highly toxic Na2 Cr2 O7 to reach high hydrogen evolution reaction (HER) Faradaic efficiencies. It is therefore important to find alternatives either to replace Na2 Cr2 O7 or reduce its concentration. RESULTS: The Na2 Cr2 O7 concentration can be significantly reduced by using Na2 MoO4 as an electrolyte co‐additive. Na2 MoO4 in the millimolar range shifts the platinum cathode potential to less negative values due to an activating effect of cathodically deposited Mo species. It also acts as a stabilizer of the electrodeposited chromium hydroxide but has a minor effect on the HER Faradaic efficiency. X‐ray photoelectron spectroscopy (XPS) results show cathodic deposition of molybdenum of different oxidation states, depending on deposition conditions. Once Na2 Cr2 O7 was present, molybdenum was not detected by XPS, as it is likely that only trace levels were deposited. Using electrochemical measurements and mass spectrometry we quantitatively monitored H2 and O2 production rates. The results indicate that 3 μmol L −1 Na2 Cr2 O7 (contrary to current industrial 10–30 mmol L −1 ) is sufficient to enhance the HER Faradaic efficiency on platinum by 15%, and by co‐adding 10 mmol L −1 Na2 MoO4 the cathode is activated while avoiding detrimental O2 generation from chemical and electrochemical reactions. Higher concentrations of Na2 MoO4 led to increased oxygen production. CONCLUSION: Careful tuning of the molybdate concentration can enhance performance of the chlorate process using chromate in the micromolar range. These insights could be also exploited in the efficient hydrogen generation by photocatalytic water splitting and in the remediation of industrial wastewater. © 2023 The Authors. Journal of Chemical Technology and Biotechnology published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry (SCI).